HACOR Score in Predicting Non-invasive Ventilation Failure in Acute Decompensated Heart Failure and AECOAD Patients - Yong Hup Teh; Mohd Zahir Amin Mohd Nazri; Abdul Muhaimin Noor Azhar; Rabiha Mohd Alip (Eurasian Journal of Emergency Medicine, 2022)

(untitled)
Aim:To compare the diagnostic accuracy of HACOR score in predicting non-invasive ventilation (NIV) failure among acute exacerbation of chronic obstructive airway disease and acute decompensated heart failure patients, and study the correlation of HACOR score with a length of stay and hospital mortality rate.Materials and Methods:A prospective observational study was conducted in the Emergency Department of Hospital Melaka. We enrolled patients who presented with acute respiratory distress and started them with NIV. The efficacy of the HACOR score is evaluated at several interval time points, before NIV initiation, 1 h, 2 h post NIV initiation.Results:HACOR score is much lower in NIV success subgroups and 100% NIV failure rate for the HACOR score more than 7 at 1 h and 2 h of NIV. With a cut-off value of more than 5 in 1 h of NIV, the diagnostic power is 86.27% with a sensitivity of 62.50% and specificity of 90.70%. While at 2 h of NIV the HACOR score of more than 5, its diagnostic power is 87.50% a sensitivity of 50% and specificity of 95%. In 0-2 hours of NIV, area under the curve for predicting NIV failure was 0.788, 0.868 and 0.925, respectively.Conclusion:The HACOR has good diagnostic accuracy when it is assessed at 1-2 h of NIV. It is convenient to use it to assess the efficacy of NIV especially for heart failure patients. However, HACOR score was a weak predictor of mortality in our study. The length of hospital stay was also found to be longer for those who failed to respond to NIV in our study.